The Effectiveness of PBL Model Assisted by Prezi Media on Students' Critical Thinking Ability and Concept Understanding - Restuti, Merdhenita; Rusdarti, Rusdarti; Sunarso, Ali (Journal of Primary Education, 2021)
Combining strategies, approaches, methods, and learning material is characteristic of today's learning models innovation. This study aims to (1) determine the validity of the PBL model supported by Prezi Media in Social Studies instruction and (2) determine the effectiveness of the PBL model assisted by Prezi Media on students' critical thinking abilities and conceptual knowledge. This research used a quasi-experimental approach with a Nonequivalent Control Group. The study was done in two schools, with the experimental class being 2 Kaliajir Primary School and the control class being 3 Petir Primary School. The data-gathering technique employed was an observation, description, and a short entry test. The data analysis technique was a prerequisite test for conducting research, including the normality and homogeneity tests. Meanwhile, hypothesis testing using expert validators, independent sample t-test, and N-Gain test were performed. The findings indicated that (1) the PBL model enhanced by Prezi media was valid for application in Social Studies education, and (2) the PBL model enhanced by Prezi media improved students' critical thinking skills and conceptual understanding. The study concludes that the PBL model, aided by Prezi media, is appropriate for social studies education and effect on students' critical thinking abilities and conceptual knowledge.